2005
DOI: 10.1196/annals.1327.010
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Expression of Phenotypes of Different Cell Lineages in the Rat and Mouse Pituitary

Abstract: As studied by single cell RT-PCR of pituitary hormones, we demonstrated that the pituitaries of rats and mice contain a subpopulation of cells that express two or more hormone phenotypes typically belonging to lineages that are branched separately early during embryonic development, such as glycoprotein hormone alpha-subunit (alphaGSU) mRNA + PRL mRNA, alphaGSU mRNA + POMC mRNA, and POMC mRNA + GH or PRL mRNA. GnRH in vitro selectively expands the population of cells coexpressing alphaGSU mRNA + PRL mRNA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…2a and 4a). Previous histological studies have described subpopulations of somatotropes in rat and pig [47][48][49] , including cells co-expressing Prl and Gh [50][51][52] . Recent scRNAseq analysis of murine pituitaries also resolved somatotrope sub-populations 1,53 .…”
Section: Discussionmentioning
confidence: 99%
“…2a and 4a). Previous histological studies have described subpopulations of somatotropes in rat and pig [47][48][49] , including cells co-expressing Prl and Gh [50][51][52] . Recent scRNAseq analysis of murine pituitaries also resolved somatotrope sub-populations 1,53 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Subburaju and Aguilera (Subburaju & Aguilera, 2007) found that only a minor proportion of BrdU labeled nuclei corresponded to cells stained with ACTH or the corticotroph precursor marker, T-pit (Pulichino et al, 2004). Reports of co-localization of ACTH in pituitary cell types other than corticotrophs, have suggested that mature pituitary cells can cross-differentiate (Denef et al, 2005). However, the lack of co-localization of BrdU stained nuclei in lactotrophs, thyrotrophs, somatotrophs or gonadotrophs, shown in this study is against this possibility.…”
Section: Alternative Actions Of Vp In the Pituitary On Mitogenesismentioning
confidence: 99%
“…Somatomammotropes and other co-secreting pituitary cells are a welldescribed phenomenon in normal mice, rats, and humans and in somatotropinomas, including the rat GH3 cell line [40][41][42] . Notably, the presence of important pools of cells secreting both GH and PRL has been repeatedly confirmed by single cell transcriptomic analysis [43][44][45] . As in other settings, increased body size and bone growth (vertebrae and long bones) due to GH/IGF-1 elevation was accompanied by decreased fat mass and increased lean mass in the Ghrhr Gpr101 mice versus wild-type controls (See Fig.…”
Section: Discussionmentioning
confidence: 85%